Ultrasound‐assisted hot air drying characteristics of Phyllanthus emblica. (1st February 2023) - Huang, Wenyang; Huang, Dan; Qin, Yiting; Zhang, Yixiao; Lu, Yijun; Huang, Shuai; Gong, Guiliang
Abstract: The ultrasound‐assisted hot air drying characteristics of Phyllanthus emblica was investigated in this paper. The effects of hot air temperature (60°C, 65°C, 70°C, and 75°C), ultrasonic pretreatment time (2, 4, 6, and 8 min), and ultrasonic power (200, 250, 300, and 350 W) on the drying rate, energy consumption, color change, and rehydration rate were evaluated and compared. It was found that the drying rate of Phyllanthus emblica increased with the hot air temperature. The drying time of Phyllanthus emblica with ultrasonic pretreatment was reduced by 10.0%, 25.0%, 21.4%, and 9.0% at 60°C, 65°C, 70°C, and 75°C, respectively. However, the hot air drying was not proportionally promoted by the increase of ultrasonic power or the extension of pretreatment time. Only an appropriate ultrasonic power or pretreatment time can not only improve the drying rate and rehydration rate, but also reduce the energy consumption and the total color change of the dried samples. A new drying model that considered the influences of hot air temperature, pretreatment time, and ultrasonic power was developed to fit the drying process. The results showed that the new model can accurately predict the hot air drying process of Phyllanthus emblica with and without ultrasonic pretreatment. Practical applications: Phyllanthus emblica contains a variety of nutrients and has various biological activities. However, the harvest period and shelf life of Phyllanthus emblica is very short, and the fruit is prone to mildrew and browning after picking, which in turn leads to the loss of its nutritional and economical value. Thus, for the long‐term preservation of Phyllanthus emblica, drying techniques are needed. In the food industry, hot air drying is widely used due to its low cost and easy operation; however, it also has some disadvantages such as long drying time, the oxygen‐rich drying environment. These shortcomings lead to a low quality of dried materials. Ultrasonic pretreatment before hot air drying can improve drying efficiency without adversely affecting the drying quality of the material. In recent years, ultrasonic pretreatment before food drying has become a research hotspot. Abstract : The ultrasound‐assisted hot air drying characteristics of Phyllanthus emblica was investigated in this paper. Appropriate ultrasonic time and power can improve the drying rate and rehydration rate of Phyllanthus emblica, and reduce the color difference and energy consumption of Phyllanthus emblica .